Waste Heat Recovery and Utilization of Advanced Compressed Air Energy Storage System - Xiankui WEN; Xiang LI; Tongtian DENG; Jingliang ZHONG; Suobin WANG; Shi LIU (Zhongguo dianli)
Compressed air energy storage is a kind of energy storage technology that has developed rapidly in recent years, which can realize energy storage and release. In order to avoid heat loss during the operation of the system, a method to recover and utilize the waste heat of the system exhaust gas and the heat exchange working fluid is proposed. On the basis of the original heat recovery system, a low expansion ratio expander is added. The converter absorbs the waste heat of the working fluid and enters the expander to do work to increase the output power of the expansion unit and improve the system efficiency. By using Aspen Plus software to establish a four-stage advanced compressed air energy storage system model under steady-state conditions for simulation. The influence of the these two factors on the system efficiency and output power is explored by changing the expander exhaust pressure and the regulator valve outlet pressure, The simulation results show that the method increases the total output power of the advanced compressed air system and improves the system efficiency.